2006
DOI: 10.1021/jf060737t
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Method for Extraction of Astaxanthin from Green Alga Haematococcus pluvialis

Abstract: Haematococcus pluvialis is one of the potent organisms for production of astaxanthin, a high value ketocarotenoid. Astaxanthin is accumulated in thick-walled cyst cells of Haematococcus. The thick cell wall is made up of sporopollenin-like material, algaenan, which hinders solvent extraction of astaxanthin. In the present study, an improved method for extraction of astaxanthin without homogenization of cells is reported. Extractability of astaxanthin from cyst cells was evaluated by treating cells with various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
113
1
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(131 citation statements)
references
References 15 publications
7
113
1
7
Order By: Relevance
“…Ash contents (mineral composition) in the algae are probably due to the concentration of inorganic compounds in the medium in which the algae grew, although ash content varied within each group. In fact, average ash content in this study was lowest than that found by Sarada et al (2006) with 4.6% dry weight for H. pluvialis.…”
Section: Discussioncontrasting
confidence: 81%
“…Ash contents (mineral composition) in the algae are probably due to the concentration of inorganic compounds in the medium in which the algae grew, although ash content varied within each group. In fact, average ash content in this study was lowest than that found by Sarada et al (2006) with 4.6% dry weight for H. pluvialis.…”
Section: Discussioncontrasting
confidence: 81%
“…The reported biomass productivities range from 0.03 to 0.6 g L pretreated by a mechanical means to disrupt the rigid cell walls, followed by a spray-drying process to produce dry biomass powder. If astaxanthin is the final product, a conventional solvent-based extraction method or supercritical fluid extraction can be applied to wet or dry Haematococcus biomass to obtain concentrated astaxanthin extracts (Bubrick 1991, Mendes-Pinto et al 2001, Nobre et al 2006, Sarada et al 2006, Krichnavaruk et al 2008). …”
Section: Mass Cultivation Of Haematococcus Pluvialis and Chlorella Zomentioning
confidence: 99%
“…The yeast Xanthophyllomyces dendrorhous (Phaffia rhodozyma) and the microalgae Haematococcus pluvialis (H. pluvialis) are known as the main microorganisms capable of synthesizing astaxanthin 27 . A number of studies have been carried out to determine the best conditions to synthesize and extract astaxanthin from these microorganisms [28][29][30] . H. pluvialis accumulates higher amounts of ketocarotenoids in cytoplasmic lipid vesicles and has been reported to be the richest source of natural astaxanthin 14 , reaching 9.2mg/g cell 27 .…”
Section: Astaxanthin Sourcesmentioning
confidence: 99%